2019
DOI: 10.1111/psyp.13328
|View full text |Cite
|
Sign up to set email alerts
|

Associations between digit ratio (2D4D), mood, and autonomic stress response in healthy men

Abstract: The ratio between the length of the second (index) and the fourth (ring) finger (2D4D) is a putative biomarker of prenatal testosterone (T) exposure, with higher exposure leading to a smaller ratio. 2D4D has further been linked to mental and somatic disorders. Healthy male Swiss recruits (N = 245; Mage = 20.30 years) underwent a psychosocial stress test. Mood and salivary alpha‐amylase (sAA) were assessed before and after the stress test, while heart rate (HR) and heart rate variability (HRV) were measured con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The study was conducted during autumn 2011 and spring 2012. The present analysis was part of a broader study of biological and psychological characteristics of recruits to the Swiss Armed Forces [ 28 , 61 , 62 , 63 , 64 , 65 ]. However, the present results have not previously been published and therefore are novel.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted during autumn 2011 and spring 2012. The present analysis was part of a broader study of biological and psychological characteristics of recruits to the Swiss Armed Forces [ 28 , 61 , 62 , 63 , 64 , 65 ]. However, the present results have not previously been published and therefore are novel.…”
Section: Methodsmentioning
confidence: 99%
“…The present analysis was part of a larger study of biological and psychological characteristics of recruits to the Swiss Armed Forces [50,51,56,[60][61][62]. Data have not previously been published or presented in this form.…”
Section: Procedures and Study Designmentioning
confidence: 99%
“…However, the research so far has not yielded conclusive results. In the case of depression, some studies reported null results [39][40][41][42][43][44] , while others found significant positive as well as significant negative associations with 2D:4D. Moreover, all significant results were restricted to either female or male participant groups, with no study reporting a significant relationship between depression and 2D:4D in both sex groups: There was one significant positive 45 and one significant negative 46 association in females, as well as two significant positive 47,48 and two significant negative 49,50 associations in males.…”
mentioning
confidence: 99%